ANALYSIS OF CHROMIUM (Cr) HEAVY METAL CONTENT IN TILAPIA (Oreochromis niloticus) FROM EX-COAL MINE AREA IN THE KERTA BUANA VILLAGE TENGGARONG SEBERANG - Maasje Catherine Watulingas (PROSIDING SEMINAR KIMIA, 2015)
There has conducted research to determine the metal content of chromium (Cr) in tilapia (Oreochromis niloticus). This study was conducted to determine the metal content of chromium in the nila fish with different sizes of fish weight, history of sampling sites (lakes former coal mine) and laboratory activities aimed to determine levels of heavy metals chromium in tilapia. Determination of heavy metals using atomic absorption spectrophotometry. The results showed that levels of Chromium on tilapia in the lake ex-coal mine has the standard quality. Based on ISO 7387: 2009, the levels of Chromium on tilapia is not suitable for consumption and based on the levels of heavy metals were analyzed in a variety of sizes do not have the weight that make significant differences.